Mediating Role of Collaboration on Transformational Leadership and Performance Contracts in Road Agencies in Kenya. - Githui, John Ngatia; Ragui, Mary; Nyakundi, Augustus Onchari (Human Resource and Leadership Journal, 2024)
Purpose: Type of leadership that can be considered effective, in the current set of environments would demand collaboration, listening skills, influence, and flexible adaptation to the existing environment in contrary to command and control systems in organizations. This study investigated the mediating role of collaboration to the relationship between transformational leadership and performance contracting in road agencies in Kenya. Operationalization of variables included transformational leadership as independent variable, performance contracting as the dependent variable and collaboration as the mediating variable. This study was guided by theories of transformational leadership and public value. Methodology: The study adopted mixed methods approach where data was collected through questionnaires and structured interviews and target population for the research was all staff members in top management and officers in job group 5 (five) and above for three road agencies in Kenya. The road agencies included Kenya National Highway Authority (KeNHA), Kenya Urban Roads Authority (KURA) and Kenya Rural Roads Authority (KeRRA). The study utilized descriptive and inferential statistics used data analysis where regression was computed to determine correlations between independent, mediating and dependent variables. Findings: From the study findings and results, the relationship between transformational leadership and performance contracting in road agencies in Kenya was noted to be partially mediated by collaboration as p value was (p< 0.05). Collaboration was therefore noted as a very important component in an organization as employees are able to achieve their performance targets with ease as different sections and individuals support each in the process of performance contracting in road agencies in Kenya. This study recommends to policy makers in road agencies in Kenya to create a conducive environment of collaboration and teamwork as the same would enhance both individual and collective performance which ultimately influence levels of achievement of set targets in performance contracts in these organization. Unique contributor to theory, policy and practice: This study recommends further areas of research in general or overall performance of road agencies in Kenya and teamwork building processes, role of leadership in teamwork and in achieving individual and organizational performance.